Pengembangan Sistem Pendukung Keputusan Untuk Penerimaan Bantuan Beras Miskin Menggunakan Metode TOPSIS - Rizka Amalia; Budimansyah Purba, Arif; Wawan Kusdiawan; Jajang Mulyana; Supriyadi Supriyadi; Willys Willys; Wafiqah Yasmin Azhar (Politeknik Kampar, 2023)
The village of Segarjaya has conducted an eligibility survey to obtain low-quality rice, but the information collected is still inaccurate, and the assessment of the eligibility for low-quality rice is not standardized. Due to the lack of standardization and inaccuracies regarding the recipients of poor rice assistance, the community often protests. The aim of this research is to develop a DSS system capable of providing accurate data results to the assistance recipients and implementing standard evaluation criteria for the recipients of poor rice. The TOPSIS method was chosen to create the DSS system. The research procedure starts with data collection, followed by the decision matrix, determining whether the solution is positive or negative ideal, the optimal distance between solutions, and the preference values for each option. The result of this research is a DSS algorithm that can be applied to PBM, which can support the Segarjaya village authorities to be more accurate in making decisions for the recipients of poor rice subsidies.